2012
DOI: 10.2337/db11-0499
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Induces Hepatic Insulin Resistance by Activating JAK2/STAT3/SOCS-1 Signaling Pathway

Abstract: Epidemiological studies indicate that patients with Alzheimer’s disease (AD) have an increased risk of developing type 2 diabetes mellitus (T2DM), and experimental studies suggest that AD exacerbates T2DM, but the underlying mechanism is still largely unknown. This study aims to investigate whether amyloid-β (Aβ), a key player in AD pathogenesis, contributes to the development of insulin resistance, as well as the underlying mechanism. We find that plasma Aβ40/42 levels are increased in patients with hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 53 publications
7
89
0
1
Order By: Relevance
“…Third, Ab accumulates in the pancreas. 34 Zhang et al 35 found that APP/presenilin 1 (PS1) transgenic AD mice with elevated plasma Ab 40/42 levels have impaired hepatic insulin signalling and glucose/insulin tolerance and activation of the JAK2/STAT3/SOCS1 pathway. The JAK/STAT/SOCS pathway was recognized as downstream of inflammatory cytokines, by which inflammation elevates insulin resistance in the peripheral system.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Ab accumulates in the pancreas. 34 Zhang et al 35 found that APP/presenilin 1 (PS1) transgenic AD mice with elevated plasma Ab 40/42 levels have impaired hepatic insulin signalling and glucose/insulin tolerance and activation of the JAK2/STAT3/SOCS1 pathway. The JAK/STAT/SOCS pathway was recognized as downstream of inflammatory cytokines, by which inflammation elevates insulin resistance in the peripheral system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classical cytokine activators of SOCS proteins listed above, a recent study has suggested that a key regulator of SOCS1 expression in the liver might be amyloid-β, a molecule that is proposed to be responsible for the link between Alzheimer's disease and the development of liver insulin resistance [52]. Using a transgenic mouse model expressing increased levels of amyloid-β, Zhang et al [52] showed reduced insulin signalling specifically in the liver, which was associated with increased protein expression of SOCS1.…”
Section: Introductionmentioning
confidence: 97%
“…Using a transgenic mouse model expressing increased levels of amyloid-β, Zhang et al [52] showed reduced insulin signalling specifically in the liver, which was associated with increased protein expression of SOCS1. In isolated hepatocytes amyloid-β was able to increase activation of JAK2/STAT3, which resulted in elevated SOCS1 expression.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore the injection of anti Abeta-neutralizing antibodies in APPswe/PSEN1dE9 AD model mice causes decreased fasting blood glucose level and improved insulin sensitivity [31]. By examining postmortem brain tissues of AD patients at different stages, it was found that AD might be a neuroendocrine disease associated with insulin signaling.…”
mentioning
confidence: 99%
“…Some studies have suggested that the main link between T2DM and AD is the disorder in insulin signaling and it was found that plasma Abeta and Abeta 1-42 levels are increased in patients with hyperglycemia [31][32][33] and also, Abeta impairs insulin signaling in mouse liver and cultured hepatocytes by activating JAK2/STAT3/ SOCS-1 signaling pathway [31]. Furthermore the injection of anti Abeta-neutralizing antibodies in APPswe/PSEN1dE9 AD model mice causes decreased fasting blood glucose level and improved insulin sensitivity [31].…”
mentioning
confidence: 99%